The global political economy of trade protectionism and liberalization : trade reform and economic adjustment in textiles and clothing - Heron, Tony , 1971- (RIPE series in global political economy, 2012)
Examines the social, political and economic impacts of trade, paying attention to the textiles and clothing sector with respect to developing countries. This book is suitable for those studying and researching international and comparative political economy, developing area studies, economics, law and geography